Is the intraoperative air leak test effective in the prevention of colorectal anastomotic leakage? A systematic review and meta-analysis - Wu, Zhouqiao (Int J Colorectal Dis, 2016)
OBJECTIVE: The intra-operative air leak test (ALT) is a common intraoperative test used to identify mechanically insufficient anastomosis. This meta-analysis aims to determine whether ALT aids to the reduction of postoperative colorectal anastomotic leakage (CAL). METHODS: A literature search was performed to select studies in acknowledged databases. Full text articles targeting ALT during colorectal surgery were included. Quality assessment, risk of bias, and the level-of-evidence of the inclusions were evaluated. ALT methodology, ALT(+) (i.e., leak observed during the test) rate, and postoperative CAL rate of the included studies were subsequently analyzed. RESULTS: Twenty studies were included for analysis, in which we found substantial risks of bias. A lower CAL rate was observed in patients who underwent ALT than those did not; however, the difference was not significant (p = 0.15). The intraoperative ALT(+) rate greatly varied among the included studies from 1.5 to 24.7 %. ALT(+) patients possessed a significantly higher CAL rate than the ALT(−) patients (11.4 vs. 4.2 %, p < 0.001). CONCLUSIONS: Based on the available evidence, performing an ALT with the reported methodology has not significantly reduced the clinical CAL rate but remains necessary due to a higher risk of CAL in ALT(+) cases. Unfortunately, additional repairs under current methods may not effectively decrease this risk. Results of this review urge a standardization of ALT methodology and effective methods to repair ALT(+) anastomoses.